Controlling Solution‐State Aggregation and Solid‐State Microstructures of Conjugated Polymers by Tuning Backbone Conformation. Issue 16 (13th April 2022) - Wu, Hao‐Tian; Yao, Ze‐Fan; Xu, Zhe; Kong, Hua‐Kang; Wang, Xin‐Yi; Li, Qi‐Yi; Wang, Jie‐Yu; Pei, Jian
Abstract: Molecular ordering of conjugated polymers both in solution‐state aggregates and in solid‐state microstructures is a determining factor of the charge transport properties in optoelectronic devices. However, the effect of backbone conformation in conjugated polymers on assembly structures is still unclear. Herein, to understand such backbone conformation effect, three novel chlorinated benzodifurandionge‐based oligo( p ‐phenylene vinylene) (BDOPV) polymers are systematically developed. These BDOPV‐based polymers exhibit significantly twisted backbone conformation (near 90° interunit torsion angle) between conjugated units, which can prevent polymer chains from forming ordered assembly structures by increasing conformational energy penalty in closely packed chains. A higher rotational barrier of the torsion angle would further prevent polymer chains from assembling, finally resulting in nonaggregated chains in solution and highly disordered solid‐state packing structures. This work will deepen the understanding of the relationship between polymer backbone conformation and assembly structures, contributing to the exploration of the structure–property relationship of polymers. Abstract : In this article, the effect of backbone conformation in conjugated polymers on assembly structures is systematically investigated. A new conjugated polymer building block of Cl4 BDOPV is developed and adopted to demonstrate that large torsion angles between conjugated units and high rotational barriers prevent the polymers from forming ordered aggregates and microstructures.